Bifunctional Ag‐based catalyst for NOx reduction with E‐diesel fuel. Issue 6 (23rd April 2014) - Kim, Pyung Soon; Cho, Byong K.; Nam, In‐Sik; Choung, Jin Woo
Abstract The excellent low‐temperature deNOx performance of Ag/AlF3/Al2O3 by simulated E‐diesel fuel has been achieved, mainly due to the multiple roles of AlF3 impregnated onto Al2O3. It increases the formation of the highly dispersed Ag ions and the catalyst surface acidity as well as the formation of the reaction intermediates such as cyanides and isocyanates. A plausible process for the formation of the surface composition of Ag/AlF3/Al2O3 has been proposed by using the results from XPS and FTIR.